Clinical efficacy of grepafloxacin in respiratory infections and its pharmacokinetics in sputum - Narui, Kouji; Nakamori, Yoshitaka; Inagawa, Hiroko; Nakatani, Tatsuo; Tsuboi, Eiyasu; Nakata, Koichiro (Japanese Journal of Chemotherapy, 1995)
We evaluated the clinical efficacy and safety of grepafloxacin (GPFX) in a phase 2 study in a total of seven patients with respiratory infections. GPFX was administered orally at a dose of 150 to 300mg daily. The time course of the serum and sputum concentrations was evaluated after administering a 300mg dose to one patient, and pharmacokinetic analysis was also performed. The subjects included one case each of bronchial asthma and diffuse panbronchiolitis, and five cases of bronchiectasis. Clinical response was good in three cases, fair in one and poor in two. Two strains of Haemophilus influenzae were eradicated, while three strains of Pseudomonas aeruginosa persisted in spite of their susceptibility to GPFX. One patient had headache and lumbago as well as chest discomfort four hours after taking GPFX. No abnormal laboratory findings were observed. The peak concentration of GPFX in sputum (four hours after administration) was 2.31μg/ml, almost two-fold that in serum, suggesting its efficacy in respiratory infections.